Perspektif Bimbingan dan Konseling di Indonesia Masa Kini dan Masa Depan - Kurniawan Dwi Madyo Utomo (Journal of Counseling and Humanistic Studies, 2025)
Guidance and Counseling needs to respond to the problems faced by students in the context of their time. A school counsellor in providing guidance and counselling services needs to take into account the context of the time. This research aims to (1) identify challenges faced by school counselors at this time and in the future; and (2) explore the guidance and counseling perspectives at this time and in the future. The  research method is library research. The research found that the developmental perspective in guidance and counseling  applied today did not meet the needs of students from a variety of backgrounds. In the future guidance and counseling will deal with the multicultural and social justice issues. Therefore, school counselors need to build multicultural competencies and are willing to be a social justice advocate so that they can help students develop their capacities fully.